ANALISIS STRATEGI PROMOSI JASA MAKE-UP ARTIST MELALUI MEDIA SOSIAL (STUDI KASUS MUA RIAS ATHIF) - Wilna Julia; Muhammad Rahmat; Sari Wulandari (Jurnal Inovasi Penelitian, 2022)
MUA Rias Athif's make-up service is one of the service businesses engaged in facial make-up. MUA Rias Athif's make-up services serve wedding, graduation, and other make-up services. Where the clients are women, of course, starting from schoolchildren to adults, with various make-up needs they want. In the era of growing, there are more and more other make-up services, which have promoted their services through social media, so from this to find out MUA Rias Athif's make-up services, how is the promotion strategy in social media. This study describes the form of promotion strategy in social media used by MUA Rias Athif. The research design used is a qualitative descriptive type of research. The method of data collection in this study is documentation because it is the owner of his own business. The instruments used are photos of activities and make up fortopolio and testimonials in the form of videos. The data analysis techniques, data presentation, and drawing conclusions. This research refers to the theory of the promotion mix which contains promotions through several social media such as WhatsApp, Public Relations which affect the increase in new clients, Personal Selling (Personal Selling) direct communication between business owners and prospective clients, Direct Marketing (Direct Marketing) social media as a place to promote makeup results and video testimonials from clients to attract the attention of potential clients.